Digital culture and the construction of Islamic political discourse: Islamist women’s subjectivation on Facebook - Sulbi Sulbi; Inayah Rohmaniyah; Alim Roswantoro (Universitas Dian Nuswantoro, 2025)
This article examines how digital discursive practices on Facebook produce a regime of truth in Islamic politics and shape the political subjectivation of Islamist women within the Muslimah News Com community. Using a qualitative critical discourse approach integrated with the Social Psychology of Protest, the study analyzes posts and comment interactions that frame social and economic crises as structural failures of democratic capitalism while promoting Islamic governance as an alternative normative system. The findings show that Facebook functions as a cultural arena where meaning is collectively produced, reproduced, and stabilized through repetitive framing, symbolic opposition, emotional mobilization and social validation. Grievances related to social inequality and corruption are transformed into ideological consciousness, collective identity, and moral emotions, which, in turn, generate collective efficacy. The normalization of Islamic political discourse occurs through continuous opposition between democracy and Sharia-based governance, reinforced by participatory engagement and digital resonance. The study concludes that Islamic political truth in digital spaces is constructed through the interplay of discourse, identity formation, emotional mobilization, and perceived collective agency. Theoretically, this research contributes to the literature by integrating Foucauldian discourse analysis with the social-psychological dimensions of mobilization, highlighting how digital platforms operate as infrastructures of power-knowledge in shaping contemporary religious-political subjectivities.